Pengaruh Motivasi dan Minat Belajar Terhadap Hasil Belajar IPA Siswa SDN Tabaringan 5 - Siti Fatima; Andi Besse Marda; Nurhayati Selvi; Ince Prabu Setiawan; Nur Afni (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to 1) determine the effect of learning motivation on science learning outcomes in third grade students at SDN Tabaringan 5, 2) determine the effect of interest in learning on science learning outcomes in third grade students at SDN Tabaringan 5, 3) Knowing the simultaneous influence of motivation and interest in learning on science learning outcomes in third grade students at SDN Tabaringan 5. This type of research is quantitative using the Ex Post Facto method. The subjects in this study were class III students at SDN Tabaringan 5, totaling 27 students. The sampling technique used in this research is saturated sampling (census). Data collection techniques using observation, questionnaires, documentation and learning outcomes tests. The results showed that there was a simultaneous influence of motivation and interest in learning on science learning outcomes for third grade students at SDN Tabaringan 5, as evidenced by multiple linear regression tests, Fvalues scores (56.678) > Ftable (3.39). Based on the calculation results, the variables > motivation (x1) and interest (x2) in learning have an effect of 82.59% on science learning outcomes (y) and the other 17.5% is influenced by other factors that are not being studied.